If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -1X + 2 = 9 Reorder the terms: 4 + 2 + -1X = 9 Combine like terms: 4 + 2 = 6 6 + -1X = 9 Solving 6 + -1X = 9 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -1X = 9 + -6 Combine like terms: 6 + -6 = 0 0 + -1X = 9 + -6 -1X = 9 + -6 Combine like terms: 9 + -6 = 3 -1X = 3 Divide each side by '-1'. X = -3 Simplifying X = -3
| 4c-2=6 | | 3x-2(8-5x)=12x | | 6/x-1=3/6 | | 1+d+1.4=d+2.4 | | 48-4x=x | | 60+60*0+1=1 | | -12w+5c+70=-80+y | | 3=4a+2b+c | | 6/x=2/7 | | 1/6z+2/3=-3 | | h=15t^2+90t+10 | | Y-2+-1x= | | (3x+2)(34x+99)=4 | | x+15-26+6=x | | 24=12b+8c | | X-2x+2+3x= | | (4y+1)(5y+7)= | | 2x=32 | | -6(x-6)=36 | | senx+1=cosx | | -5(x-3)+2x= | | 3/4=b/32 | | 5x+-3=2(3+x) | | 4/8+2= | | 4(a-6)=4a-10 | | f(-27.018)=31.572x-17.741 | | 4a-(a-5)=23 | | f(6.2)=31.572x-17.741 | | 6z+24=6(2+4) | | -b*-1=-3m+1 | | 8-7x-5-7x=5 | | (2x^2-2x-4)+(-4x^2+5x-1)= |